HIV the pursuit of an elusive vaccine - Coulson, Annie (BioTechniques, 2023)
In 1984, when it was discovered that the HIV-1 virus caused AIDS, the US Health and Human Services Secretary, Margaret Heckler, declared that a vaccine would be available within 2 years. So why, 40 years on, are we still searching for an HIV vaccine? [Formula: see text]